PROFIL PEMECAHAN MASALAH SISWA SMP NEGERI 1 PALASA DALAM MENYELESAIKAN SOAL PROGRAMME FOR INTERNATIONAL STUDENT ASSESSMENT (PISA) KONTEN QUANTITY: Profile of Problem Solving of SMP Negeri 1 Palasa in Solving Problem of Programme for International Student Assessment (PISA) Content Quantity - Yulviyana Yulviyana; Baharuddin Paloloang; Dasa Ismaimuza (Jurnal Elektronik Pendidikan Matematika Tadulako, 2025)
The purpose of this research is to identify the problem-solving profile of junior high school students as they solve PISA problems with a quantity content. The type of this Research is descriptive research with qualitative approach. There were two students in this research as subject, both having high and medium ability levels. Data were collected by test and interview methods. Problem solving in this research refers to Polya's problem solving steps. The results of the research show: (1) At the step of understanding the problem, students with high and medium ability levels can identify things that are known and asked at the given problem; (2) At the step of devising a problem-solving plan, students with high and medium ability levels can explain the problem-solving plan and relate it to what is known and asked about the problem so that it leads to problem solving; (3) At the step of carrying out  the problem-solving plan, students with high and medium ability levels can write down the steps of completion based on the solution plan that has been made and obtain the final result; (4) At the step of looking back  the process and results of problem solving, students with high and medium ability levels can adjust the answers obtained with the questions asked in the problem and can make conclusions at the end of solving the problem.